The universal sense : how hearing shapes the mind - Horowitz, Seth S. (New York : Bloomsbury, 2012)
"Every day, we are beset by millions of sounds-ambient ones like the rumble of the train and the hum of air conditioner, as well as more pronounced sounds, such as human speech, music, and sirens. But how do we process what we hear every day? This book answers such revealing questions as: Why do we often fall asleep on train rides or in the car, and what does it have to do with hearing? What is it about the sound of fingernails on a chalkboard that makes us cringe? Why do city folks have trouble sleeping in the country, and vice versa? Why can't you get that jingle out of your head? Starting with the basics of the biology, neuroscientist and musician Seth Horowitz explains how sound affects us, and in turn, how we've learned to manipulate sound: into music, commercial jingles, car horns, and modern inventions like cochlear implants, ultrasound scans, and the mosquito ringtone. Combining the best parts of This is Your Brain on Music and How We Decide, this book gives new insight into what the sounds of our world have to do with the way we think, feel, and interact"--
In the beginning was the boom -- Spaces and places : a walk in the park -- Listeners of the low end : fish and frogs -- The high-frequency club -- What lies below : time, attention, and emotion -- Ten dollars to the first person who can define "music" (and get a musician, a psychologist, a composer, a neuroscientist, and someone listening to an iPod to agree) -- Sticky ears : soundtracks, laugh tracks, and jingles all the way -- Hacking your brain through your ears -- Weapons and weirdness -- Future noizes -- You are what you hear.
Includes bibliographical references (p. 285-293) and index.
Keywords: Hearing -- Physiological aspects; Sound -- Psychological aspects; SCIENCE / Acoustics & Sound; SCIENCE / Life Sciences / Human Anatomy & Physiology; Auditory Perception; Hearing -- physiology; Hearing -- Physiological aspects; Sound -- Psychological aspects